PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KINERJA GURU SMP NEGERI 4 DI KOTA TARAKAN - Kristianto, Theodorus; Hoko, Angela Marici Ina (Journal Education and Government Wiyata, 2025)
Education is a strategic factor in developing high-quality human resources, and teachers play a key role as the spearhead of the learning process. This study aims to analyze the effect of training and motivation on teacher performance at SMPN 4 Tarakan. This research employed a quantitative method with a survey approach. The population consisted of all teachers at SMPN 4 Tarakan, with a sample of 36 teachers selected using a total sampling technique. The research instrument was a questionnaire developed based on training indicators by Noe (2017), motivation by Maslow (1943), and teacher performance by Mangkunegara (2017). Data were analyzed using multiple linear regression with the help of SPSS software. The findings reveal that training has a positive and significant effect on teacher performance, motivation has a positive and significant effect on teacher performance, and training and motivation simultaneously have a significant effect on teacher performance. These results highlight that improving teacher performance can be achieved through effective training programs and consistent motivation. This study implies the importance of school strategies in designing teacher professional development programs oriented toward enhancing education quality.